2017
DOI: 10.18196/ftl.2220
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Survey of Technology Use, Teaching, and Technology-Related Learning Experiences among Pre-Service English Language Teachers in Indonesia

Abstract: This study aims to design a survey instrument that can be used to collect information on the relationships between the ICT-related learning experiences of the English language pre-service teachers in Yogyakarta, Indonesia, and their technological pedagogical content knowledge (TPACK). Qualitative and quantitative research methods were used to analyse the degree of the reliability and validity of the instrument. The result suggests that this instrument meets the general requirements to be used in a larger scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Digital technology is continuously changing. Teachers are required to have the ability to keep up and adapt to the changes [59].…”
Section: Tpck Skills Of Indonesian Language Teachersmentioning
confidence: 99%
“…Digital technology is continuously changing. Teachers are required to have the ability to keep up and adapt to the changes [59].…”
Section: Tpck Skills Of Indonesian Language Teachersmentioning
confidence: 99%
“…The Ministry of National Education also states that teachers need to integrate Information and Communication Technology (ICT) in the process of learning and teaching technology mastery. According to Ciptaningrum (2017), ICT has the potential to contribute to improving the English language proficiency of Indonesian students. For example, the use of technology through social media has become an innovative alternative in improving students' English writing skills (Inderawati, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several researchers have shown that nowadays technology lifestyle changes the monotonous classroom activity to be an active learning (Kompa, 2012in Ciptaningrum (2017. The ubiquitous availability of technology media is also inserted in the traditional way of teaching and learning (A, 2019;Ekrem & Recep, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as the significant substance for research, TPACK has been already investigated in English Language Teach ing (ELT) context (Ekrem & Recep, 2014;Ersanli, 2016;Köse, 2016) and also rapidly discussed in Indonesian context in recent years (Aniq et al, 2019;Ciptaningrum, 2017;Limbong, 2016). Most of the researches are unison focus on the practical EFL teachers" (abbreviated as PETs) perception or voices in facing the TPACK.…”
Section: Introductionmentioning
confidence: 99%